Controlling of Pneumatic Muscle Actuator Systems by Parallel Structure of Neural Network and Proportional Controllers (PNNP) - Al-Ibadi, Alaa; Nefti-Meziani, Samia; Davis, Steve (Frontiers in Robotics and AI, 2020)
This article proposed a novel controller structure to track the nonlinear behavior of the pneumatic muscle actuator (PMA), such as the elongation for the extensor actuator and bending for the bending PMA. The proposed controller consists neural network (NN) controller laid in parallel with the proportional controller (P). The parallel neural network-proportional (PNNP) controllers provide a high level of precision and fast-tracking control system. The PNNP has been applied to control the length of the single extensor PMA and the bending angle of the single self-bending contraction actuator (SBCA) at different load values. For further validation, the PNNP applied to control a human-robot shared control system. The results show the efficiency of the proposed controller structure.